(untitled) (Docentes 2.0 Journal, 2020)
One of the demands assigned to teachers is to change their practices as it is a necessity of the digital age. For this reason, it is essential to distance yourself from educational practice, analyze it in each of its dimensions, therefore, in this way discover its meaning in order to make interpretations from different angles. The project aimed to rethink the teaching practices mediated by Learning and Knowledge Technologies (TAC) from the implementation of the teacher support program in the digital age. Guided professional development through follow-up activities included collaborative work between tutors and colleagues with the goal of improving their practice. The facilitation model had as a learning center, teachers considered as autonomous professionals with the ability to modify their practice. The qualitative approach was used to perform an inductive analysis of the different data collected. The results obtained from different data collection strategies showed beliefs, experiences, resistance, knowledge, strengths, and weaknesses that teachers possessed when integrating educational technologies in the classroom. Regarding the conclusions drawn, it can be expressed that despite the benefits that the implementation of technologies in education brings, some teachers fear the arrival of new digital tools because they consider that they can displace them from their work. The attitude of teachers towards the integration of educational technologies posed a challenge regarding the paradigm shift in their professional culture.